THE INFLUENCE OF QUALITY OF WORK LIFE, WORK FACILITIES, AND ORGANIZATIONAL COMMITMENT ON JOB SATISFACTION - Ida Ayu Iswari Pidada; Ni Putu Rikaandriani (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2021)
Introduction: This study aims to analyze the influence of quality of work life, work facilities, and organizational commitment on job satisfaction at the Karma Royal Jimbaran hotel.Methods: The population in this study are employees of Karma Royal Jimbaran with a total sample of 30 people. Data collection techniques in this study are using documentation, interviews, observations, and questionnaires. The data analysis technique uses multiple linear regression analysis.Results: The results shows that quality of work life, work facilities and organizational commitment have positive and significant effect on employee job satisfaction at Hotel Karma Royal Jimbaran.Conclusion and suggestion: For Hotel Karma Royal Jimbaran, the results of this study can be used as a theoretical basis to increase employee job satisfaction by increasing the quality of work life which is implemented by paying attention to the welfare of employees through the salaries received by employees, improving work facilities which are implemented by optimizing the availability of transportation for employees. thus supporting the speed and timeliness of employees' work also increasing organizational commitment to employees, this is implemented by building a conducive work environment and giving employees proper rights so that it will increase employee loyalty and employee commitment to continue working at the Karma Royal Jimbaran Hotel.